Growth Performance, Body Measurements and Live Weight Estimation of Tülü (Bactrian × Dromedary F1) Calves from Birth to Six Months of Age - Atakan Koç; Alkan Çağlı (Turkish Journal of Agriculture: Food Science and Technology)
A hybrid camel Tülü (Bactrian male x Dromedary female F1) males are preferred in camel wrestling, which is a culture unique to Anatolia. In this study, changes of live weight (LW), daily weight gain (DWG), and body measurements (BMs) of Tülü calves in the first 6 months of age in a farm in Aydın province, Türkiye, were determined as well as developing equations to estimate LW from body measurements. Tülü calves average birth weight (BW) was 34.7±1.80 kg and reached 175.3±3.38 kg at the age of 6 months with a 0.768±0.03 kg DWG during this time. Although the monthly total weight gains and monthly DWG averages of the calves in the first 6 months were similar, the changes in monthly LW and BMs were statistically significant (P<0.01). Abdominal girth (AG) alone can be used to predict LW in the analysis performed to estimate LW from body measurements by stepwise regression (R²=95.62%). In conclusion, Tülü calves had relatively high growth rate in their first six months of age, and unlike other livestock species, instead of hearth girth (HG), AG that includes the hump can be used to estimate LW of Tülü calves.